Techniques of economic forecasting: an account of the methods of short-term economic forecasting used by the Governments of Canada France the Netherlands Sweden the United Kingdom and the United States with an introduction by C W McMahon - Organisation for Economic Co-operation and Development (Paris, 1965)
This book reveals processes in which government economists might compare their respective methods and procedures for forecasting.
asm; 25/01/19
Loans
Keywords: Economic forecasting; Canada; the Netherlands; France; Sweden; United Kingdom; United States